State of Arts: Structural Behavior of Confined Short Columns With Different Concrete Types Subjected to Uniaxial Loading (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The study of the structural performance for a short Columns is essential for the applications in our interest as a high-rise buildings, and bridges are Concerned, and the load bearing capacity with Stability are required: So long, the short Column's, defined by their slenderness ration Which exhibit unique stress distribution and Failure mechanisms under uniaxial loading. Nowadays, the advancements in concrete technology have introduced various Concrete Types including high-strength concrete (HSE) and fiber-reinforced Comerele (FRC) a these developments , along with innovative Confinement methods such as steel tube, fiber-reinforced polymer (FRP) wraps, and shape memory alloys (SMA), have to improve the load -Carrying capacity and ductility of Short Columns , So that to achieve these, we have to apply materials that restrict lateral deformation, resulting to improving compressive strength and overall stability, This research synthesizes existing studies on confined shorts columns of different concrete types and focusing on the impact of confinement techniques and material properties On structural performance and failure behavior . The study examines found from experimental and numerical analysis on various hybrid columns. So this research prides insights for optimizing column design to enhance safety and resilience in structural applications.